Burnout and its Factors in Healthcare Workers Involved in Providing Health Care for Patients With COVID-19 at Different Stages of the Pandemic - A. B. Kholmogorova; S. S. Petrikov; A. Y. Suroyegina; O. Y. Mikita; A. A. Rakhmanina; A. P. Roy (Неотложная медицинская помощь, 2020)
Abstract. In the context of the pandemic, when healthcare professionals are forced to work under extreme stress and an increased threat of infection, research on professional burnout and emotional maladjustment of medical workers is gaining particular relevance around the world.Aim of study. To assess the severity of symptoms of depression and anxiety, professional burnout and emotional distress among the employees of the N.V. Sklifosovsky Research Institute for Emergency Medicine, providing care to patients with COVID-19 in the current period (July). To compare them with the indicators of a mixed sample of medical workers from different institutions and regions surveyed in the first months of the pandemic (March–April), and also to highlight the main factors of distress and protective factors.Material and methods. The research methods were combined into a Google form, and participation in the research was anonymous. Of the 175 people who were sent questionnaires, filled out the form completely 120 people (69% samples), of which 43 men and 77 women, 54.2% were doctors of different specialties; 40% were nurses, the rest of the categories accounted for 5.8% of the sample. The mean age of the respondents was 36.1 years (from 21 to 61 years).Results. The data obtained on the indicators of mental distress are generally consistent with international data: 8.3% of the surveyed demonstrate symptoms of depression of moderate and severe severity according to the Beck’s Depression Scale; 6.7 % noted the presence of suicidal thoughts; 29.3% had symptoms of anxiety of moderate and high severity according to the Beck’s Anxiety Scale. And 35% had high level of emotional exhaustion according to the Maslach Burnout Inventory. Nevertheless, the data obtained indicate a greater mental well-being of employees of the N.V. Sklifosovsky Research Institute in comparison with a mixed sample of specialists surveyed in March - April. The limitations of such a comparison are indicated, which are associated with differences in organizational affiliation and the composition of specialists. Anxiety for family members (noted by 54.7%) and fear of infection (noted by 38.3%) were most often named as an important factor of distress in the entire sample of 120 people. The most significant protective factors (reducing the level of distress), noted by more than half of the employees, were information about the current situation and tasks from the management, support from family and colleagues, material incentives and the opportunity to take breaks for rest. Based on the data of the regression analysis, it is concluded that it is important to take measures for psychological relief, provide personnel with protective equipment, reduce the level of physical discomfort associated with the use of personal protective equipment and lack of sleep, explain to the staff the meaning of all measures and decisions taken, and collegial discussion of the organization of work. The quality of support from relatives, colleagues and administration helps maintain a sense of the importance of their profession and self-respect for themselves as a professional among medical personnel.